(untitled) (Research, Society and Development, 2021)
The intrauterine system (IUS) is an effective and reversible contraceptive method, very popular in emerging countries. However, in some cases, aggravating factors may occur, such as displacement of the IUS, which is a rare complication. The migration of the IUS may cause uterine perforation, either during or after insertion, which can be asymptomatic or present clinical symptoms ranging from abnormal bleeding to fistula formation. We report a case of a 31-year-old patient, IUS user, who complained of moderate pain in the hypogastric region. During a hysterectomy, it was found that the IUS was in extrauterine location.